GE_GERICHTE P/20872/2017 vom 14. November 2019 - GE Cour de justice (2019)
QUALITÉ POUR AGIR ET RECOURIR;DIFFAMATION;CLASSEMENT DE LA PROCÉDURE;DÉNONCIATION CALOMNIEUSE | CPP.319; CPP.115; CP.303; CP.304; CP.173; CP.174